Yield of sweet potato fertilized with cattle manure and biofertilizer - Oliveira,Ademar P (2010)
In Northeastern Brazil, the sweet potato is cultivated in small farms, in a family farming systems, constituting themselves an alternative way for the generation of food, employment and income. This study aimed to assess the effect of cattle manure levels and biofertilizer concentrations on the sweet potato cultivar White Queen productivity. The experiment was carried out from March to September 2007 at the EMEPA Experimental Station in Lagoa Seca, Brazil. The experimental design was randomized blocks, in split split plot 6 x 4 x 2 + 1 scheme, with four replications. The plots consisted of cattle manure levels (0, 10, 20, 30, 40 and 50 t ha-1), the subplot of biofertilizer concentrations (0, 15, 30 and 45%) and the sub subplots consisted of methods of biofertilizer application, to the soil or leaves. Also, there was an additional control treatment using N, P and K mineral fertilizer. Commercial and total root productivity was evaluated. The levels of 30.8 and 31.2 t ha-1 of cattle manure were responsible for the highest commercial and total sweet potato root productivity (17.4 and 13.1 t ha-1, respectively). Biofertilizer concentrations of 29 and 28%, applied to soil and to leaves provided, respectively, the greatest productivities of total roots (15.4 and 13.1 t ha-1), whereas concentrations of 30 and 27%, also applied to soil and leaves were responsible, respectively, for the highest commercial root productivity (11 and 9.7 t ha-1).